Chromaticats the effects of varying the fitness function on the efficiency of Cat Swarm Optimization in solving the Graph Coloring Problem - Bacarisas, Noel D. (2011)
Graph Coloring Problem (GCP) is a very well-studied optimization problem not only because of its various real-world applications but also because of the theoretical challenges that it presents. A lot of optimization algorithms were used and have shown promising results in solving GCP. Common among optimization algorithms is their use of a fitness function. Fitness functions play a key role in finding a solution and thus affect the efficiency of the algorithm. In this paper another optimization algorithm based on the behavior of cats, the CAT Swarm Optimization or CSO was able to solve all GCP instances and was able to find the optimal solution for some graph types. Also, it is shown that the nature of the solution found is affected by the fitness function used. These results indicate that CSO is a feasible algorithm in solving GCP.